The use of the Project Model Canvas tool in the planning of an educational project in a school in Canindé-CE (Research, Society and Development, 2022)
The main objective of this article is to analyze the use of the Project Model Canvas tool in the planning and execution of an educational project in a high school located in the municipality of Canindé-CE, from the point of view of a School Coordinator. Thus, a case study was developed with a qualitative approach, based on data collected with the application of a questionnaire applied to the researched subject. The applied questionnaire presents questions that characterize the academic and professional profile of the investigated, their conceptions about school projects and their knowledge about the PMC planning tool and their experiences when planning and executing a project using the tool. It was obtained from the bibliographic survey that through the PMC tool it is possible to organize a mental model of a project from 13 elements. After using the tool by the researched subject, it is possible to identify positive points, such as: the possibility of systematically reflecting the project that wants to be executed, as well as limitations, such as: some reflections made possible in a superficial way.